Enhancing the performance of germanium nanowire anodes for Li-ion batteries by direct growth on textured copper. Issue 54 (18th June 2019) - Geaney, Hugh; Bree, Gerard; Stokes, Killian; Collins, Gearoid A.; Aminu, Ibrahim Saana; Kennedy, Tadhg; Ryan, Kevin M.
Abstract : Capacity retention of directly grown Ge nanowire anodes is enhanced by replacing stainless steel with textured Cu foil current collectors. Abstract : Herein, textured Cu foil is presented as an attractive current collector substrate for directly grown Ge nanowire (NW) anodes. Compared to planar stainless steel (SS) current collectors, textured Cu led to an increase in achievable mass loading, removal of the requirement for a catalyst deposition step, improved adhesion of the active material and dramatically enhanced capacity retention. When SS and textured Cu foil based anodes with similar areal loadings (∼1.4 mA h cm −2 ) were compared, the capacity after 250 cycles for textured Cu was 2.7 times higher than the SS anode, illustrating the key role of the current collector.